2011
DOI: 10.17305/bjbms.2011.2555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt loading on sympathetic activity and blood pressure in anesthetized two-kidney, one clip hypertensive rats

Abstract: In this study, we investigated the effects of salt loading on sympathetic pressor activity, cardiac autonomic activity, mean arterial pressure (MAP), heart rate (HR) and on the relations between them in anesthetized two-kidney, one clip (2K1C) hypertensive rats. We submitted rats to either renal artery clipping or sham operation. Distilled water or 0.5 % NaCl was given orally to the clipped and sham-operated control rats for 4 weeks. Then, MAP and HR differences between pre-and post-autonomic blockade were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Despite the lack of differences in baseline ABP of mice fed 0.1% and 4.0% NaCl, a high-salt diet transiently exaggerated 2K1C hypertension during the first 7 days, and ABP normalized thereafter. Other studies report a similar time course or no differences in ABP between high- and low-NaCl groups ( 10 , 15 , 45 , 49 , 51 ). The mechanism(s) by which a high-salt diet transiently exaggerates ABP in 2K1C mice is not known but may include a higher cardiac output due to the dietary salt loading, enhanced cardiovascular reactivity by high salt to surgical stress, or an interaction between high salt and RAAS.…”
Section: Discussionmentioning
confidence: 72%
“…Despite the lack of differences in baseline ABP of mice fed 0.1% and 4.0% NaCl, a high-salt diet transiently exaggerated 2K1C hypertension during the first 7 days, and ABP normalized thereafter. Other studies report a similar time course or no differences in ABP between high- and low-NaCl groups ( 10 , 15 , 45 , 49 , 51 ). The mechanism(s) by which a high-salt diet transiently exaggerates ABP in 2K1C mice is not known but may include a higher cardiac output due to the dietary salt loading, enhanced cardiovascular reactivity by high salt to surgical stress, or an interaction between high salt and RAAS.…”
Section: Discussionmentioning
confidence: 72%
“…It has been previously reported that even short-term oral or central salt loading increases sympathetic activity, especially when salt is directly infused into the brain stem of rats (21,37). The mechanism by which a HS load activates the sympathetic nervous system has not been completely elucidated, but a recent study (10) has suggested the involvement of oxidative stress.…”
mentioning
confidence: 99%
“…For instance, an abnormal baroreflex control of heart rate has been linked to the pathogenesis of essential hypertension [2], [3] and impaired baroreflex sensitivity (BRS) has been demonstrated in salt-sensitive hypertension [4]- [6]. The baroreflex system buffers the changes in BP by the beat-tobeat regulation of the heart rate and peripheral vascular resistance [7].…”
Section: Introductionmentioning
confidence: 99%